A dual-emission CdTe@ZIF-8/CDs@MIPs nanocomposite for visual and ratiometric lysozyme sensing - Liu, Xiqing; Wang, Tao; Wang, Yongqing (Microchemical journal, 2025)
Fluorescence technology enabled highly sensitive, real-time and multi-scenario detection of lysozyme (Lys). However, fluorescent nanomaterials suffer from aggregation-induced quenching, environmental interference and lack of selective recognition capability. In this work, the ZIF-8 was used as a framework to support red and blue fluorescence quantum dots for constructing ratiometric fluorescence sensor. At the same time, combined with molecular imprinting technology, a Molecular Imprinting Polymers (MIPs)-based ratiometric fluorescence sensor was designed for improving the sensitive and selective. The MIPs-based ratiometric fluorescence sensor exhibited highly sensitively and selectively for the detection of lysozyme. Benefited from ratiometric design, the sensor could realize the effect of visual detection of Lys and the limit of detection (LOD) was reached 0.048 mg/L. The HPLC method was used to further confirm the sensor has the potential for practical application. Furthermore, to the demand of an affordable and portable strategy for visual detection Lys, a dexterous and inexpensive test paper was made in this work. A MIPs-based ratiometric fluorescence strategy using CDs, CdTe QDs and ZIF-8 for highly selective and sensitive determination of lysozyme with naked-eye observation. [Display omitted] •ZIF-8 was used as a carrier for CDs and CdTe QDs to avoid the agglomeration quenching of quantum dots.•Molecular imprinting technology realized the selective recognition of the target by the sensor.•A fast and convenient ratiometric-based fluorescence test paper was designed for the detection of lysozyme.•The HPLC method was used to further confirm the sensor has the potential for practical application.